Devenir un professionnel de la professionnalisation des étudiants : un changement accompagné dans les cultures et pratiques des enseignants et enseignants-chercheurs ? - Stéphanie Tralongo (Éducation et Socialisation)
Professionalization at University Institutes of Technology is a term of art that has the strength of obviousness. However, for newly recruited teachers or associate professors, vocational teaching is nothing obvious but is rather related to socialization. By focusing on two teaching methods (tutoring and the " personal and vocational project" module), we will show how definitions, cultures, students’ professionalizing practices come to the teachers. Acculturation thus needs implementing institutional support systems for teachers’ socialization. We will highlight the dynamic relationship between organization, schemes and socially diverse ownership.